2009
DOI: 10.1038/sj.bdj.2009.258
|View full text |Cite
|
Sign up to set email alerts
|

Case studies on implant removal influencing the resolution of inferior alveolar nerve injury

Abstract: Introduction Nerve injury during implant placement is a preventable, serious complication with major medico-legal implications. The incidence of implant related inferior alveolar nerve (IAN) injuries varies from 0-40%. This article presents four cases of IAN injury following mandibular implant placement with early removal, referred to the oral surgery department, King's College Hospital, London. Objectives To assess sensory disturbance and recovery in patients with implant related IAN injury and assess whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 21 publications
2
82
0
10
Order By: Relevance
“…Their injuries resolved fully suggesting that early removal may facilitate nerve injury resolution. This is indeed also recommended in a previous study 17 and supported by the fact that several patients in this study had their implants removed between 30 hours and 6 days and none made a recovery. This reinforces the recommended practice of undertaking 'Homecheck' with in 12 hours post surgery to enable the patient to report ongoing neuropathy, which may dictate early removal of the implant is required.…”
Section: Postoperativelysupporting
confidence: 87%
See 1 more Smart Citation
“…Their injuries resolved fully suggesting that early removal may facilitate nerve injury resolution. This is indeed also recommended in a previous study 17 and supported by the fact that several patients in this study had their implants removed between 30 hours and 6 days and none made a recovery. This reinforces the recommended practice of undertaking 'Homecheck' with in 12 hours post surgery to enable the patient to report ongoing neuropathy, which may dictate early removal of the implant is required.…”
Section: Postoperativelysupporting
confidence: 87%
“…Appropriate planning, assessment and training should be undertaken in order to minimise injury. 17 Avoidance of nerve injury is sometimes attempted by using techniques including nerve lateralisation and alveolar distraction, however, these procedures are themselves high-risk, and may be more likely to result in injury. Interestingly, 25% of 110 edentulous patients included in a randomised controlled clinical trial presented with a degree of altered IAN function before implant placement, perhaps suggesting the need for pre-operative neurosensory evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Concernant les critères implantaires, nous avons observé ( [13]. Le rapport de cas de Leckel évoque également la pose de 2 implants en position 36 et 37 [14].…”
Section: Fig 2 Onset Characteristics Of Neuropathic Pain For Each unclassified
“…Ce qui paraît également intéressant dans notre cohorte est la proportion de cas de douleur neuropathique chronique post-implantaire au maxillaire, soit 37,5 % des patients (3/8 patients). La plupart des rapports ou série de cas [13,18,15,16] font référence aux douleurs neuropathiques chroniques post-implantaires suite à une lésion sur le nerf alvéolaire inférieur. Cependant la lésion du nerf maxillaire et ses branches distales doit également rester une priorité diagnostique, bien que l'imagerie ne soit pas pertinente dans ce cas.…”
Section: Fig 2 Onset Characteristics Of Neuropathic Pain For Each unclassified
“…[44] Adjunctive procedures are also sometimes attempted to avoid implant nerve injury. [45] However, previous studies have indicated that regardless of the surgeon's experience, these high-risk procedures that include bone graft harvesting, posterior alveolar distraction and nerve lateralization, may be more likely to result in participate through electronic postings. Finally, members of the British Association of Oral Surgeons (BAOS) were invited to complete the online questionnaire.…”
mentioning
confidence: 99%